Overview of the rubber industry of Sri Lanka - Tillekeratne L M K (Proceedings of the First Symposium on Plantation Crop Research : Current Trends and Future Challenges,8-9 July, 2004, Sri Lanka, pp. 8-14.)
Natural rubber plant has been introduced to Sri Lanka in 1876, Entire Rubber Plantation in the South East Asia has originated from these plants, planted in Sri Lanka. The rubber extent in Sri Lanka has declined vastly since 1975. The total rubber production last year was only 91,000 mt where as the production in 1978 was 165,000 mt; nearly 65;of which is produced by the small holders. The natural rubber consumption in the country has risen to 65;of the total production. Further, raw rubber in both dry and latex forms have been imported to Sri Lanka during the past couple of years to cater to the products industry. In order to increase the raw rubber production in the country, three strategies planned: the short term strategy is to fix rain guards thereby the production can be increased within the year by over 30;; the long term strategy is to expand the plantation to non traditional areas like Monaragala and into abandoned tea lands in hilly areas; the second long term atrategy is to increase national rubber productivity to 1500 kg/ha/yr. Use of quality planting materials plays a major role in improving the productivity of rubber plantations. Nursery under the management of the Rubber Reasearch Institute of Sri Lanka (RRISL) at present, will provide the entire quality plant needs for year 2004 for the smallholders from high yielding clones developed by the RRISL without any shortage. Plant requirement for the privately owned bud wood nurseries, will also be provided by the RRISL from all the recommended clones including recently recommended RRISL clones. If all these goals are achieved, the earnings from the rubber and rubber products industries could be increased to meet 10;of the GDP value by year 2015.
Keywords: Hevea brasiliensis; Rubber industry; Rubber plantation; Rubber production; Sri Lanka